The rationale for methylene blue utility against SARS-CoV-2 infection complications - Gilberto L. Pardo Andreu (GarVal Editorial Ltda., 2021)
Context: Almost one year after the onset of COVID-19 pandemic in Wuhan, China and still no specific therapy has emerged, counting millions of dead worldwide. The association of an uncontrolled SARS-CoV-2 replication and host-dependent mechanisms in COVID-19 pathogenesis suggest that any therapeutic strategy must combine antiviral drugs and adjuvant therapy to modulate the host's responses. Owing to the multiplicity of mechanisms involved in COVID-19 pathogenic expressions, such as severe hypoxia, excessive inflammatory reaction and impaired immune response, an emerging therapeutic paradigm is the searching for agents acting as multifunctional drugs. Methylene blue (MB), the antique medication, seems to meet the above criterion. Aims: To summarize the probable beneficial effects of MB against COVID-19 supported by a discussion of the drug mechanisms of action counteracting the pathogenic mechanisms of the disease. Methods: PubMed, Google Scholar, and Scopus databases were used to collect the biomedical research on MB, and the discussed dataset finally included 150 published articles. Those COVID-19 pathogenic pathways possibly targeted by MB were critically appraised. Results: It was found that MB may act as multimodal agent by targeting simultaneously several pathogenic mechanisms of COVID-19 as hypoxic damage, hyper-inflammatory reaction and death signaling activation. It also may act as a virucidal agent by preventing virus-induced metabolic re-orientation. Its high safety profile, low cost, along with the mechanisms discussed herein might be essential criteria to test MB as an adjuvant therapy against COVID-19. Conclusions: Overall, this critical review provides theoretical grounds for MB clinical evaluation in the therapeutic management of SARS-CoV-2 infection.